رۆڵی سۆشيال ميديا لە گه‌شه‌پێدانى هۆشيارى سياسیدا (توێژینەوەیەكی مه‌يدانيیه،‌ مامۆستايانى زانكۆ حکومییەکان له‌ هه‌رێمى كوردستاندا بەنمونە) - مستەفا, پ.ی.د.رێبه‌ر گۆران; عبیدالله, م.ی.روان صبحی (Sulaimani Journal for Humanities, 2023)
This research aims to identify the role of social media in developing political awareness (a field study / teacher of public universities in the Kurdistan Region as a model). The researchers reached a set of results, the most important of which are: University teachers use social media at a large level and size, and political topics are among the most famous and important topics by the research sample in terms of their interest and reading on social media, and social media contributes to forming political awareness about political issues and topics among the respondents in a big way.